Autism and attention-deficit/hyperactivity symptoms as risk factors of school attendance problems in youth with rare genetic disorders - Stian Orm; Ingrid Tien; Jeffrey Wood; Krister Fjermestad (Discover Psychology)
Abstract Background School attendance problems are common among youth with autism spectrum disorder (ASD) or attention-deficit/hyperactivity disorder (ADHD). We investigated the role of ASD and ADHD symptoms in school attendance problems among youth with rare genetic disorders, which are present in fewer than 1 in 2000 people. Method Parents completed the Social Responsiveness Scale (SRS) and the Child Behavior Checklist (CBCL) about their youth with a rare genetic disorder (N = 93; M age = 13.2 years, SD = 2.3, 62.4% females, 37.6% males). School attendance problems were assessed with the CBCL school anxiety and truancy items. The data were analyzed using generalized linear mixed models. Results One-fourth of the sample (27%) displayed school anxiety, and 11% displayed truancy. More ASD symptoms (OR = 1.04, 95% CI [1.02, 1.06]) and ADHD symptoms (OR = 1.22, 95% CI [1.07, 1.38]) were associated with a higher risk of school anxiety. The analyses indicated that the associations between ASD and ADHD symptoms and school anxiety could be accounted for by internalizing symptoms. Externalizing symptoms were associated with truancy. There was no relationship between ASD/ADHD symptoms and truancy. Conclusions More ASD and ADHD symptoms in youth with rare genetic disorders are associated with an increased risk of being afraid of school, but not truancy. The risk entangled by ASD and ADHD symptoms can be accounted for by the commonly co-occurring internalizing symptoms. Assessment of ASD and ADHD symptomatology in youth with rare genetic disorders may be important to target educational and psychosocial support and prevent school attendance problems.